Hubungan Pengetahuan dengan Perilaku Pemberantasan Sarang Nyamuk dalam Upaya Pencegahan Penyakit Demam Berdarah di Desa Sumbermulyo Bambanglipuro Bantul - Siti Arifah (Journal of Health (JoH), 2019)
Dengue hemorrhagic fever (DHF) is an endemic disease in Bantul district. Counselling of pandemic Society and mosquito eradication program has been conducted to increase knowledge and the chance of happened behavioral change the effort to eliminate behavior of eradication mosquitonest. But infect Dengue Hemorragic Fever insidensi still be high. There are three factor play a part in infection of DHFdisease, that is virus agent, human being and environment, beside Aedes aegypti mosquito as infection vektors such as.Goal of: The relationship of knowledge with the effort to eliminate behavior of eradication mosquitonest in the attempt preventing of disease dengue in Sumbermulyo Bambanglipuro Bantul. Method: This research was a quantitative research with descriptive method survey. 77 people was taken by using Non Probability sampling technique with Purposive Sampling method. Test Validity is product moment pearson and test reliabilitas is cronbach alpha and continued with Chi Square data analysis. Prevalency value < 1.Chi-square was used to analize data. Result of: to the result of this study was 0,453. This result indicatied that there was no relationship between knowledge and PSN's behaviors in this Village Sumbermulyo Bambanglipuro Bantul. It is recommended to increase the community knowledge about the PSN program by using the appropriate strategy. The level of knwledge and the effort to eliminate behavior of eradication mosquitonest